Perbaikan Selisih Stock Gudang SMT Pada Sistem ERP Microsoft Dynamics AX Menggunakan Metode Fishbone - Hana Silvia Dwi Putri; Sekti Agus Pamungkas (Jurnal Jaring SainTek, 2020)
Supplies play an important role in supporting the smooth running of production activities, at the warehouse of SMT PT. SDI has problems that can interfere with the smooth running of production, namely there is a difference between the actual stock of raw materials and the stock in the Microsoft Dynamics AX ERP system which can cause material shortage but there is a demand for material for production, which can cause the production process to stop, change the production schedule, and even to the point of not fulfilling customer desires. This study aims to analyze the causes and make improvements to the difference in SMT warehouse stock, the Fishbone Diagram method is used to analyze the causes of the difference in stock so that it can be widely known to its roots, so that appropriate improvements can be made. The results of the research are the causes and improvements to the difference in SMT warehouse stock, the cause of human factors, namely the low ability of the repair workforce by providing education and training, admin in production, incorrect picking repairs by making a picking list checking check sheet, and delivery of materials that are not suitable for repair by double check the results of the preparation and making big part list.